Hallazgos ecográficos del apéndice cecal asociados a la apendicitis aguda complicada en pacientes atendidos en el Hospital Apoyo Iquitos "César Garayar García", 2021 - Reátegui del Castillo, Martín Remberto (2023)
Acute appendicitis is the most common disease that requires surgical treatment in emergencies, complicated cases being those that must be identified promptly and for this a discriminatory test is of the utmost importance. For this reason, the present work aims to determine the ultrasound findings of the cecal appendix associated to the complicated acute appendicitis. An observational, analytical, cross-sectional and retrospective study was developed, which included 162 patients treated at the Hospital Apoyo Iquitos "César Garayar García" during the year 2021. Concluding that there is a statistically significant association between the presence of appendicoliths visible by ultrasound and the complicated acute appendicitis (OR = 3.5, p < 0.001).